Creating Value Together? Stakeholder Participation and Tensions in a Public Cultural Initiative - Rita Bendaravičienė; Katryna Žėkienė (Journal of Creating Value, 2026)
Cultural capital initiatives are viewed as platforms for social inclusion, urban change and value creation for stakeholders. However, how value is co-created, especially in small cities, remains underexplored. This study investigates value co-creation in the Lithuanian Capital of Culture initiative through a case study of Druskininkai (2025). Drawing on Service-Dominant Logic and the DART framework (Dialogue, Access, Risk-sharing and Transparency), the study adopts an interpretive qualitative approach to examine stakeholder participation and collaborative governance. Empirical data were collected through 11 semi-structured interviews with representatives from local government, cultural institutions, business organizations and community groups and were analyzed using thematic analysis. The findings show the initiative created cultural, social, symbolic, economic and personal value but also revealed uneven participation and influence among stakeholders. While dialogue among institutional actors was strong, peripheral participants had limited access, transparency and risk-sharing. The study highlights that inclusive cultural initiatives can still reproduce participation gaps within local governance. The article contributes to emerging debates on the relational and governance dimensions of value co-creation in public cultural initiatives and offers practical insights to strengthen more inclusive stakeholder participation.